Cuscus (Phalangeridae) hunting by Napan communities at Ratewi Island, Nabire, Papua - FREDDY PATTISELANNO (Society for Indonesian Biodiversity, 2007)
Cuscus hunting by Napan communities at the Arui village of Ratewi Island was conducted from July to September 2007 by interviewing hunter respondent and direct observation to the field. Twenty households were selected as respondent with the criterion hunting and utilizing cuscus. The study indicated active hunting is performing mostly for consumption purpose, using several combinations of hunting tools from traditional to modern ones, found around mix forest or combination between primary and secondary forest. Cutting the cuscus nesting tree resulted negative impact on the cover and food sources for the future conservation purpose. Two species of cuscus occurred in the study site, they were common cuscus (Phalanger orientalis) and spotted cuscus (Spilocuscus maculatus), and based their qualitative traits both species can be distinguished morphologically.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: cuscus hunting, Napan, Ratewi Island, Papua.